IMPLICATIONS OF GOVERNMENT LEGAL SUBJECT STATUS AS ONE OF THE CAUSES OF TAX DISPUTES ON PRODUCTION SHARING CONTRACTS FOR THE OIL AND GAS INDUSTRY IN INDONESIA - Mulyo Basuki (Yustisia Jurnal Hukum, 2020)
Supreme Court Decision Number 2424/B/PK/Pjk/2020 states that the PSC (Production Sharing Contract) is a Government to Business ("G to B") agreement that applies domestic taxes. Therefore, in tax disputes over Branch Profit Tax (BPT) between a Permanent Establishment Taxpayer (BUT) and the Director-General of Taxes, the Supreme Court's decision uses a 20% domestic tax rate instead of 10% in accordance with the Tax Treaty. This study elaborates how the Government's position in the production sharing contract with the private sector or PE is related to Indonesian and international tax law. The main issues raised are the Government's position as a legal subject in the PSC agreement and the process associated with regulating BPT in international taxation. This is a library study with the juridical-normative approach method. The results showed that the Government acts as a subject of civil law in the PSC agreement. However, in the PSC contract, the relationship between the state and the private sector or PE (BUT) in natural resource management must be carried out using a public relationship by giving concessions or permits full of state control and power. For instance, the Indonesian tax law does not apply when there is a tax treaty. The Taxation Law in Indonesia cannot unilaterally interpret taxes on BPT based on Indonesian domestic provisions.